Mali : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Mali reached the completion point under the enhanced HIPC initiative on March 6, 2003. Staff recommends that the Board determine that Mali qualifies for MDRI debt relief.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Mali